Mixed connective tissue disease: state of the art on clinical practice guidelines. (18th October 2018) - Chaigne, Benjamin; Scirè, Carlo Alberto; Talarico, Rosaria; Alexander, Tobias; Amoura, Zahir; Avcin, Tadej; Beretta, Lorenzo; Doria, Andrea; Guffroy, Aurelien; Guimarães, Vera; Hachulla, Éric; Krieg, Thomas; et al.
Abstract : Mixed connective tissue disease (MCTD) is a complex overlap disease with features of different autoimmune connective tissue diseases (CTDs) namely systemic sclerosis, poly/dermatomyositis and systemic lupus erythematous in patients with antibodies targeting the U1 small nuclear ribonucleoprotein particle. In this narrative review, we summarise the results of a systematic literature research which was performed as part of the European Reference Network on Rare and Complex Connective Tissue and Musculoskeletal Diseases project, aimed at evaluating existing clinical practice guidelines (CPGs) or recommendations. Since no specific CPGs on MCTD were found, other CPGs developed for other CTDs were taken into consideration in order to discuss what can be applied to MCTD even if designed for other diseases. Three major objectives were proposed for the future development of CPGs: MCTD diagnosis (diagnostic criteria), MCTD initial and follow-up evaluations, MCTD treatment. Early diagnosis, epidemiological data, assessment of burden of disease and QOL aspects are among the unmet needs identified by patients.